GAYA KEPEMIMPINAN SITUASIONAL DALAM ORGANISASI PENDIDIKAN ISLAM: TELAAH KONSEPTUAL PAUL HERSEY DAN KEN BLANCHARD - Apsari Arisanti Elfreda; Ali Nasith (Jurnal Manajemen Pendidikan, 2026)
Objective: This study aims to examine the concept of situational leadership within the context of Islamic educational organizations, with particular emphasis on how the Hersey-Blanchard model can conceptually be implemented in the management of human resources in Islamic educational institutions. Methods: This study employs a qualitative descriptive-analytic approach with library research as the primary data collection technique. Data were obtained from scientific journals and primary literature published between 2020 and 2026. Results: The review reveals that situational leadership is conceptually relevant for Islamic educational organizations due to its flexibility, which aligns with the diversity of competencies and motivations among human resources within such institutions. Novelty: This study produces a conceptual framework integrating the situational flexibility of the Hersey-Blanchard model with Islamic values, encompassing the principles of amanah (trustworthiness), musyawarah (deliberative consultation), and uswah hasanah (exemplary conduct), as a normative foundation for human resource management in Islamic educational organizations. These findings offer a theoretically robust model that bridges modern leadership science with Islamic pedagogical values.